Theurapeutic Response of Neoadjuvant Chemotherapy between Platinum and Ifosfamide Combination and Platinum, Vincristine and Bleomycin Combination in Cervical Carcinoma Stage IB2 - Nuryanto, Kartiwa H; Purbadi, Sigit (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To evaluate the theurapeutic response and acute toxicity of neoadjuvant chemotherapy between the combination of Platinum and Ifosfamide, and the combination of Platinum, Vincristine and Bleomycin in Cervical Carcinoma Stage IB2 and then continued with radical hysterectomy and pelvic lymphadenectomy. Method: Thirteen samples received neoadjuvant chemotherapy of Platinum and Ifosfamide and 17 samples received neoadjuvant chemotherapy of Platinum, Vincristine and Bleomycin, after receiving the neoadjuvant chemotherapy, clinically complete response samples underwent radical hysterectomy and pelvic lymphadenectomy (PI VS PVB = 3 VS 1). Histopathology examination was performed to evaluate the presence of malignant viable cells at the cervix, pelvic lymph node metastasis and parametrium metastasis. Acute toxicity evaluation was performed based on gastrointestinal, genitourinarius and hematology sign and symptom. Result: Theurapeutic response of PI is 1.12 higher than PVB (p>0.05). Subanalysis of group response of PI is 1.962 higher than PVB. PI and PVB have the same risk to have pelvic lymph node metastasis, but not parametrial metastasis. There were no differences in terms of the risk of gastrointestinal, genitourinarius and hematologic toxicity between PI and PVB. Conclusion: There was no statistical difference in clinical and pathological response, and also in acute toxicity between the two combination (p>0.05). [Indones J Obstet Gynecol 2016; 1: 47-51] Keywords: acute toxicity, cervical carcinoma stage IB2, neoadjuvant chemotherapy, response